PECULIARITIES OF STRESS MANIFESTATION IN THE STUDENT ENVIRONMENT: 1-SON 2-TO’PLAM IYUL 2023 yil - International Islamic Academy of Uzbekistan Laboratory assistant at the Department of Psychology of Religion and Pedagogy, Abduganieva Diyora (Ta'lim innovatsiyasi va integratsiyasi, 2023)
The concepts of stress and stress resistance are considered. A review of research in the field of studying stress and methods of increasing stress resistance of students of higher educational institutions is carried out, as well as current research directions in these areas are identified